New syllabus primary mathematics workbook 3B - Yee, Dr. Foong Pui (Karachi Oxford University Press., 2024)
New Syllabus Primary Mathematics Workbook 3B is a supplementary resource designed to extend and reinforce the mathematical concepts introduced in the Primary Mathematics 3 textbook. Covering topics such as fractions, measurement, time, geometry, and word problems, the workbook provides a variety of exercises to help students practice and solidify their understanding. The structured activities are aimed at enhancing problem-solving skills and promoting independent thinking. With a focus on real-life applications and practical scenarios, this workbook is an essential tool for helping students develop confidence and competence in mathematics as they progress through more complex topics.